In-class social networks and academic performance: how good connections can improve grades - Gomes Jr., Luiz (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2019)
Understanding how different variables affect student performance is an important requirement for improving educational practices. Since humans are highly social beings, social factors should play a significant role in the academic context. This paper analyzes the impact on academic performance of social indicators such as students friendship circle and in-class clustering. The analysis is based on data from six different classes of the topic Databases taken by students of computing-related majors. We assessed students’ friendship circle in terms of density (sociability) and also quality (grades) of their friends. The paper shows results with strong, statistically relevant relationships between the social factors and student performance. Among other results, the analysis indicates that (i) students with higher social capital tend to perform better, and (ii) students with friends with higher grades have better chances of recovering from a low exam grade.